PC.111 Survey of Sildenafil Use for Treatment of Persistent Pulmonary Hypertension (PPHN) in Tertiary Neonatal Intensive Care Units (NICU) in England and Wales. (9th June 2014) - Murphy, AP; Turnbull, C; Nesbitt, V; Guratski, V; Kamalanathan, A
Abstract : Introduction: Sildenafil is increasingly used to treat PPHN secondary to chronic lung disease in neonates. Severity of PPHN has been linked to increased mortality at two years. 1 There is no national guideline advising clinicians on dosage or weaning schedules for use of Sildenafil in neonates. Methods: A telephone survey of tertiary level neonatal units in England and Wales (n = 48) was conducted in December 2013 and January 2014. Neonatal consultants were contacted to ensure robust data. In the event a consultant was not available, staffs employed by the unit for at least 24 months (Specialist registrar, Advanced Neonatal Nurse Practitioner (ANNP) or nursing sister) were surveyed. Results: The response rate was 90% (n = 43/48). Sildenafil was used frequently (>5 patients per year) in 12% (n = 5), infrequently, (1–5 patients per year) in 23% (n = 10) and rarely (<1 per year) in 51% (n = 22). Majority of units had used Sildenafil within the last 6 months 49% (n = 21). 60% (n = 26) used Sildenafil only after discussion with Cardiologists, 35% (n = 15) commenced Sildenafil after discussion with neonatal colleagues. No unit had fixed indications for commencement of Sildenafil. Amongst those with a guideline (n = 6); the initial dose varied between 250–300 mcg/kg commenced between 4 and 12 hourly. Guidelines on two units were unclear on rate of increase of Sildenafil. No guideline stipulated weaning/stopping practice. Conclusion: Sildenafil is infrequently used in NICU, however only 6 units did not use Sildenafil in the past 24 months. Variability in practice amongst units mirrors the need for a national consensus guideline.